2016
DOI: 10.1186/s12883-016-0691-3
|View full text |Cite
|
Sign up to set email alerts
|

The relation between angioarchitectural factors of developmental venous anomaly and concomitant sporadic cavernous malformation

Abstract: BackgroundPast studies found that cerebral developmental venous anomaly (DVA) is often concurrent with cavernous malformation (CM). But the reason of the concurrency remains unknown. The purpose of this study was to confirm whether angioarchitectural factors relate to the concurrence and which angioarchitectural factors can induce the concurrency.MethodsDVA cases were selected from the records of the same 3.0 T MR. The DVA cases was divided into two group which are DVA group and DVA concurrent with CM group. 8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 26 publications
(32 reference statements)
0
11
0
Order By: Relevance
“…Clinical data obtained from other studies showed that DVAs form dilated, deep medullary veins with caput-medusae formations 90. MRI data obtained from other studies also showed that when DVAs coexist with CCMs, both lesions are connected,88 91 92 reaffirming their close relationship and possible shared signalling pathways. Other studies have reported that when both CCMs and DVAs coexist in the same individual, the haemorrhagic risk increases, 33%–48%,75 93 raising the possibility that CCM signalling cascades merge with PI3K signalling pathways from which DVAs originate.…”
Section: Introductionmentioning
confidence: 75%
See 3 more Smart Citations
“…Clinical data obtained from other studies showed that DVAs form dilated, deep medullary veins with caput-medusae formations 90. MRI data obtained from other studies also showed that when DVAs coexist with CCMs, both lesions are connected,88 91 92 reaffirming their close relationship and possible shared signalling pathways. Other studies have reported that when both CCMs and DVAs coexist in the same individual, the haemorrhagic risk increases, 33%–48%,75 93 raising the possibility that CCM signalling cascades merge with PI3K signalling pathways from which DVAs originate.…”
Section: Introductionmentioning
confidence: 75%
“…However, additional data indicates that the haemodynamic effects of DVAs may be the actual trigger for the initial formation of CCMs 79. Perfusion data generated from a haemodynamic study in DVAs indicated that the restrictive effects on the venous drainage caused by DVAs are sufficient to cause local venous hypertension, leading to CCM formation, or even the propensity of these flanking vessels (or CCM lesions) to bleed, suggesting that initiation of CCMs or occurrence of haemorrhagic CCMs is a consequence of angioarchitectural factors of DVAs 79 88 94 95. These findings raise another possibility that the coexistence of DVAs influence the haemorrhagic occurrence in CCM lesions in which elevated blood pool in the surrounding brain parenchyma as well as increased local venous blood pressure may be key factors for the haemorrhagic events in CCM lesions since CCMs without DVAs tend to bleed at the same frequency.…”
Section: Introductionmentioning
confidence: 92%
See 2 more Smart Citations
“…Conversely, mutations in the three known CCM genes were rarely detected in sCCM lesions, which instead resulted associated mainly with somatic mutations in other genes [ 10 , 11 , 12 ], suggesting that fCCM and sCCM lesions may have a distinct genetic origin. Moreover, patients with fCCM often present multiple cerebral cavernomas (up to several hundreds), which are typically not associated with a DVA [ 13 ], while patients with sCCM commonly present a single lesion of various sizes (from mm to several cm) that is frequently associated with a DVA, suggesting the possibility of a different developmental mechanism [ 13 , 14 , 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%